THE EFFECT OF MODERNIZATION OF TAX ADMINISTRATION SYSTEM, TAX SANCTIONS AND QUALITY OF TAX SERVICES ON INDIVIDUAL TAXPAYER COMPLIANCE WITH TAX KNOWLEDGE AS A MODERATING VARIABLENORTH BATAM PRIMARY - Muhammad Fajar Erdiawan; Bambang Satriawan; Muammar Khaddafi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study examines the Effect of Modernization of Tax Administration System, Tax Sanctions and Service Quality on Individual Taxpayer Compliance with Tax Knowledge as a Moderating Variable of North Batam Pratama Tax Service Office. Quantitative research is a process of finding knowledge that uses data in the form of numbers as a tool to find information about what we want to know. The data analysis technique in this study uses Partial Least Square (PLS) which is a Multivariate Analysis in the second generation using structural equation modeling (Structural Equation Model/SEM). The results of the study Modernization of Tax Administration System has a significant effect on Individual Taxpayer Compliance. Tax Sanctions have a significant effect on Individual Taxpayer Compliance. Tax Service Quality has a significant effect on Individual Taxpayer Compliance. Tax Knowledge has a positive and significant effect in moderating the effect of Modernization of Tax Administration System on Individual Taxpayer Compliance. Tax Knowledge does not have a positive and significant effect in moderating the effect of Tax Sanctions on Individual Taxpayer Compliance. Taxation Knowledge has a positive and significant effect in moderating the influence of Tax Service Quality on Individual Taxpayer Compliance. The magnitude of the influence of the contribution of the Tax Administration System Modernization variable, the Tax Sanction variable and the Tax Service Quality variable on the Individual Taxpayer Compliance variable is 108.8%.